Cutaneous Crohn's disease treated with infliximab and 4 years of follow up. (18th June 2013) - Yoong, Corinne; Schofield, Clare; Rodins, Karl; Faulkner, Catherine
Abstract Metastatic Crohn's disease (MCD) is a rare, non‐contiguous cutaneous manifestation of Crohn's disease. To date, there have been only four reports in the literature of an effective treatment of this condition with infliximab and there are no long‐term follow‐up studies on adult MCD patients treated with infliximab. We present a case of MCD treated with infliximab with 4.5 years of follow up.